Accelerating ray-casting for semitransparent image using Bi-directional skipped distance transforms - Sepsirisuk, Kasemsuk; Ungpinitpong, Phittaya; Lertprasert, Polsart; Sangworasil, Manas (My University, 2002)
This paper shows a method for speeding up the ray-traversal process of volume viewing. The algorithm acceleration is achieved by skipping empty regions defined for each background voxel of the volume in pre-processing step. Background voxels are labeled by a value, which is equal to the voxel distance to the nearest foreground voxel. The algorithm starts by backward traverse of the volume to find an existing point of the foreground and follows by forward traverse of the volume from an entry point of volume until it meets the existing point. This method enables a faster Tay-traversal time than traditional distance transforms.
Keywords: Distance transforms; Ray casting; Visualization